PATHOPHYSIOLOGY OF MYOCARDIAL INFARCTION - Razhabova Zebiniso Safarovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Myocardial  infarction  (MI),  commonly  known  as  a  heart  attack, occurs  due  to  the  sudden  occlusion  of  a  coronary  artery,  leading  to  ischemia  and necrosis  of  the  myocardial  tissue.  It  is  a  major  cause  of  morbidity  and  mortality worldwide.  This  article  discusses  the  underlying  mechanisms,  including atherosclerosis,  plaque  rupture,  thrombosis,  and  inflammatory  responses,  that contribute to MI pathophysiology.